Facile Method for Liquid-exfoliated Graphene Size Prediction by UV-visible Spectroscopy - Zulhelmi, Ismail; Kamal, Yusoh (AIP Publishing LLC, 2016)
In this work, an application of UV spectroscopy for facile prediction of liquid –exfoliated graphene size is discussed. Dynamic light scattering method was used to estimate the graphene flake size (<d> whilst UV spectroscopy measurement was carried out for extinction coefficient value (ε) determination. It was found that the value of (ε) decreased gradually as the graphene size was further reduced after intense sonication time (7h). This observation showed the influence of sonication time on electronic structure of graphene. A mathematical equation was derived from log-log graph for correlation between (<d>) and (ε) value. Both values can be expressed in a single equation as (<d> = (3.4 × 10−2) ε1.2).